(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2026)
The objective of the research was to find out the effect of picture series media on students’ vocabulary achievement. The research method included research design of was pre-experimental with pre-test and post-test. It aimed at knowing the effect picture series media on students vocabulary achievement at SMPN 44 Makassar. This population was the total of 20 students because the population below 100 students, so all the population was to be the sample of this research. The instrument used included observation sheet, pre-test and post-test and documentation. Next the procedure of collecting data followed the following steps. This can be seen from the average pre-test score is 70 and post-test is 80. There is a significant difference between the pre-test and post-test. The results and findings showed that students also have been successful in learning picture series media and got good result and test.